Issues of Developing Fintech Activities of Enterprises - Zilola Shomansurova (Scientific Trends, 2023)
The existence of fintech activities in this article leads to technological changes, which are carried out using other technological regime technologies. In this context, it is stated that the fintech activity of enterprises, which serve as a basis for sustainable economic development, is an important component and condition of sustainable economic development. At the same time, the analysis of the essence of fintech activity of enterprises, the issues of ensuring sustainable economic development through the development of a mechanism of innovative activity, taking into account the innovative area of the enterprise.
Keywords: FinTech, venture capital, fund, global marketing, science, risk.